Early Origin and Evolution of the Angelman Syndrome Ubiquitin Ligase Gene Ube3a - Sato, Masaaki (Frontiers in Cellular Neuroscience, 2017)
The human Ube3a gene encodes an E3 ubiquitin ligase and exhibits brain-specific genomic imprinting. Genetic abnormalities that affect the maternal copy of this gene cause the neurodevelopmental disorder Angelman syndrome (AS), which is characterized by severe mental retardation, speech impairment, seizure, ataxia and some unique behavioral phenotypes. In this review article, I highlight the evolution of the Ube3a gene and its imprinting to provide evolutionary insights into AS. Recent comparative genomic studies have revealed that Ube3a is most phylogenetically similar to HECTD2 among the human HECT (homologous to the E6AP carboxyl terminus) family of E3 ubiquitin ligases, and its distant evolutionary origin can be traced to common ancestors of fungi and animals. Moreover, a gene more similar to Ube3a than HECTD2 is found in a range of eukaryotes from amoebozoans to basal metazoans, but is lost in later lineages. Unlike in mice and humans, Ube3a expression is biallelic in birds, monotremes, marsupials and insects. The imprinting domain that governs maternal expression of Ube3a was formed from non-imprinted elements following multiple chromosomal rearrangements after diversification of marsupials and placental mammals. Hence, the evolutionary origins of Ube3a date from long before the emergence of the nervous system, although its imprinted expression was acquired relatively recently. These observations suggest that exogenous expression and functional analyses of ancient Ube3a orthologs in mammalian neurons will facilitate the evolutionary understanding of AS.